Quality of life and associated factors among family caregivers of individuals with psychiatric illness at DRH, South Wollo, Ethiopia, 2020 - Habtam Gelaye; Atsedemariam Andualem (Scientific Reports, 2022)
Abstract Mental illness results in an enormous social and economic burden not only on patients, but also on their families and communities. Many caregivers of patients with mental illnesses suffer from an extremely poor quality of life. In Sub-Saharan Africa, approximately 71% caregivers suffer from economic burden of severe mental illness. To our knowledge, no study has been conducted on quality of life of caregivers in Ethiopia. Therefore, this study aimed to assess the quality of life of family caregivers of patients with mental illness at Dessie Referral Hospital. The institution-based cross-sectional study was conducted among 398 caregivers selected using a consecutive sampling technique. The World Health Organization Quality of Life BREF was used to assess the quality of life. Logistic regression was performed and statistical significance was declared at a p-value < 0.05. 189 (47.5%) of family caregivers had poor quality of life. Being divorced, unable to read and write, primary education, being spouse, sibling and children of the patient, poor social support and high perceived stigma were significantly associated with the outcome variable. Because the magnitude of poor quality of life among family caregivers was high, family intervention programs are highly recommended to improve quality of life among caregivers.